(untitled) (Journal of Plant Disease Sciences, 2022)
Study was conducted in vitro to study the growth promotion activity and growth pattern of Pseudomonas fluorescens on different solid media. Soil samples were collected randomly from rhizosphere of citrus plants for isolation of Pseudomonas. Twenty six isolates was isolated, out of twenty six isolates eight isolates showed abiliity of siderophore production, thirteen isolates showed positiveness for IAA production, nine isolates showed phosphate solubilization and seven isolates were positive for HCN production. For growth pattern study of P. fluorescens three different media i.e. King’s B, Pseudomonas agar and nutrient agar used. All the isolates showed fast growth on King’s B followed by Pseudomonas agar and nutrient agar. Mostly Pseudomonas fluorescens produced greenish yellow coloured colonies on King’s B and Pseudomonas agar and dull yellowish coloured colony and creamy white coloured colony on nutrient agar. Fluorescent pigmentation was observed on King’B and Pseudomonas agar medium.